MATHEMATICAL MODELLING OF TECTONIC FACIES ON THE BASIS OF ACOUSTIC ANALYSIS OF METAMORPHIC ROCKS OF KRYVBAS - BEZRODNYI, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Design of tectonic facies of the carried out for the models "ferrous quartzite", "slate of biotitoviy" and "quarzite of biotitoviy", with the investigation of the acoustic and resilient properties of metamorphic breeds by cleavage.